Plant-Soil Feedbacks and Facilitation Influence the Demography of Herbaceous Alpine Species in Response to Woody Plant Range Expansion - Collins, Courtney G.; Bohner, Teresa F.; Diez, Jeffrey M. (Frontiers in Ecology and Evolution, 2019)
Plant species migrations, or range shifts, in response to changing climate are one of many interacting factors influencing plant population and community dynamics in an era of global change. Range shifts may cause novel assemblages of competing species because species may respond to changing climate at different rates. Range-expanding species may directly influence resident species through resource competition or indirectly by modifying the local environment both aboveground and belowground. Further, range-expanding plant species can create novel plant-soil feedbacks (PSFs) by altering soil microbial community structure and function and the interactions of resident plant species with microbial symbionts. These changes can have important implications for resident plant population dynamics and their ability to coexist with novel competitors. Here we test the impacts of competitive interactions and plant-soil feedbacks (PSFs) of a range-expanding sagebrush species (Artemisia. rothrockii) on the demography and population growth rates of two resident alpine plant species (Koeleria macrantha and Eriogonum ovalifolium). We use an experimental, multi-year field approach combined with integral projection modeling to determine how PSFs and competition influence species coexistence in both the historic and range expansion zone of A. rothrockii. We find that sagebrush has an overall net negative effect on herbaceous plant demography, primarily due to negative PSFs for plants growing in sagebrush-conditioned soil. However, these negative soil effects are partially buffered via facilitation effects for herbs growing under or nearby sagebrush canopies. In general, population growth rates were more sensitive to survival than other demographic rates, furthermore this sensitivity to survival was higher for herbaceous species in sagebrush soils. Identifying the major drivers of plant population dynamics and species interactions remains an important and unresolved question in ecology. PSFs are a central mechanism influencing plant species interactions, yet the majority of PSF research has made little direct connection between plant population dynamics and PSFs in situ. We believe that utilizing a field-based approach, focusing on multiple components of plant demography, is an important next step in understanding the role of PSFs and species interactions in a rapidly changing world.